2017
DOI: 10.17221/271/2015-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The Cys83Gly amino acid substitution in feather keratin is associated with pigeon performance in long-distance races

Abstract: The aim of this study was to investigate the association of the g.710T>G polymorphism in the keratin gene, which results in a cysteine to glycine amino acid change at position 83 (Cys83Gly) in feather keratin, with homing pigeon racing performance. A total of 123 homing pigeons were investigated. The data set used in this study consisted of scores from 17 short races (less than 400 km) and 11 long races (greater than 500 km) that took place in the 2011 and 2012 racing seasons (2589 race records in total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…With the growing popularity of pigeon racing as a lucrative sport, molecular approaches to the identification of genetic markers, such as SNPs, important to racing and homing phenotypes have been explored in the past [ 1 , 2 , 3 , 5 , 6 , 7 , 8 , 12 , 13 , 17 , 26 , 42 ]. The results of this study demonstrated the application of KASP as a method to detect SNPs previously identified to be associated with the racing traits of pigeons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the growing popularity of pigeon racing as a lucrative sport, molecular approaches to the identification of genetic markers, such as SNPs, important to racing and homing phenotypes have been explored in the past [ 1 , 2 , 3 , 5 , 6 , 7 , 8 , 12 , 13 , 17 , 26 , 42 ]. The results of this study demonstrated the application of KASP as a method to detect SNPs previously identified to be associated with the racing traits of pigeons.…”
Section: Discussionmentioning
confidence: 99%
“…As in [ 42 ], the currently reported method may also potentially contribute to the advancement of our understanding of polymorphisms and their relationship with observable characteristics. As more potential genetic markers are being identified to be related to desirable traits among racing pigeons [ 2 , 10 , 12 , 17 , 42 ], and considering the advantages of KASP assays compared to PCR-RFLP in terms of cost, speed, and scalability as discussed above, this study may also serve as a basis for the further development of other KASP assays to detect other single nucleotide polymorphisms in pigeons, and even in other avian species. Lastly, to the best of our knowledge, this is the first report of the use of KASP assays in any avian species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many factors affecting these traits [21], so searching for the appropriate genetic markers is crucial for this purpose. The most common types of markers in genomes are SNPs [22,23], and some of them have been used to predict racing performance in pigeons [20,21,[24][25][26].…”
Section: Short Communicationsmentioning
confidence: 99%
“…There are many tools for selection, but the most common types of markers in genomes are SNPs [Goldstein andCavalleri 2005, Jacob et al 2018], nowadays, genetic markers have been used to predict racing perform-ance in pigeons [Proskura et al 2014, Proskura et al 2015, Proskura et al 2017, Ramadan et al 2018, Dybus et al 2018. Recently, in whole-genome study, the CASK gene was marked as an important genetic factor for fast flight, long endurance, and accurate navigation was revealed [Gazda et al 2018].…”
Section: Introductionmentioning
confidence: 99%